A taxonomic revision of the subfamily Tillinae Leach sensu lato (Coleoptera, Cleridae) in the New World - Burke, Alan; Zolnerowich, Gregory (My University, 2017)
The subfamily Tillinae Leach is represented by 12 genera in the New World. In this study, eight of these genera are revised. A diagnosis and redescription of the species of Araeodontia Barr, Barrotillus Rifkind, Bogcia Barr, Cylidrus Latreille, Cymatoderella Barr, Lecontella Wolcott & Chapin, Monophylla Spinola, and Onychotillus Chapin are presented. Bogcia oaxacae Barr is designated as a junior synonym of Bogcia disjuncta Barr. One species, Cymatodera striatopunctata Chevrolat, is transferred to Lecontella. The following species are redescribed: Araeodontia isabellae (Wolcott), A. marginalis Barr, A. peninsularis (Schaeffer), Barrotillus kropotkini Rifkind, Bogcia disjuncta Barr, Cylidrus abdominalis Klug, Cymatoderella collaris (Spinola), C. morula Rifkind, C. patagoniae (Knull), Lecontella brunnea (Spinola), L. gnara Wolcott, L. striatopunctata (Chevrolat), Monophylla californica (Fall), M. pallipes Schaeffer, M. terminata (Say), Onychotillus vittatus Chapin, and O. cubana De Zayas. Transcriptions of the original descriptions of Araeodontia picipennis Barr, Bostrichoclerus bicornis Van Dyke and Monophylla cinctipennis (Chevrolat) are given. Cymatodera Gray, with approximately 130 described species, is excluded from this study due to the number of species involved. The genera Neocallotillus Burke and Callotillus Wolcott are also excluded here since these groups have been recently revised elsewhere. Collection data are provided for all species revised. Updated distribution maps are presented. Keys to New World genera and species are given and taxonomic characters of relevant importance are provided and discussed.
Citation: Burke A, Zolnerowich G (2017) Taxonomic revision of the New World Tillinae Leach sensu lato (Coleoptera: Cleridae). ZooKeys 719: 75-157. https://doi.org/10.3897/zookeys.179.21253
Keywords: Taxonomy; Cleridae; Tillinae; New World; Distribution; Description